The outsiders : - Thorndike, William N. (Harvard Business Review Press, 2012)
In The Outsiders, you'll learn the traits and methods striking for their consistency and relentless rationality that helped these unique leaders achieve such exceptional performance. Humble, unassuming, and often frugal, these "outsiders" shunned Wall Street and the press, and shied away from the hottest new management trends. Instead, they shared specific traits that put them and the companies they led on winning trajectories: a laser-sharp focus on per share value as opposed to earnings or sales growth; an exceptional talent for allocating capital and human resources; and the belief that cash flow, not reported earnings, determines a company's long-term value.